2018
DOI: 10.2147/ndt.s145046
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cost savings of pharmacogenetic testing for depression in real-world clinical settings

Abstract: The burden of depression significantly impacts the patient, the health care system, and society, at large. Medication management guided by pharmacogenetics has been shown to increase therapeutic efficacy and improve symptoms in patients diagnosed with depression, but limited data are available on the cost savings of pharmacogenetic-guided interventions outside of psychiatric clinical specialties. Our study utilizes published health care costs and clinical patient outcome data to model the economic impact of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…As cost-effectiveness is still considered a major barrier for the clinical implementation of pharmacogenetics 48 , we suggest that current genotyping microarrays constitute the most cost-effective technology with acceptable accuracy. Several studies have found pre-emptive pharmacogenetic testing cost-efficient with per-patient savings ranging from 5,962-10,667 USD [49][50][51] , despite the reported costs of pharmacogenetic testing to be over 2,000 USD 49 . Thus, both genotyping and developing tools for translating pre-existing genome-wide genotype data into clinical recommendations can be considered very reasonable healthcare investments.…”
Section: Discussionmentioning
confidence: 99%
“…As cost-effectiveness is still considered a major barrier for the clinical implementation of pharmacogenetics 48 , we suggest that current genotyping microarrays constitute the most cost-effective technology with acceptable accuracy. Several studies have found pre-emptive pharmacogenetic testing cost-efficient with per-patient savings ranging from 5,962-10,667 USD [49][50][51] , despite the reported costs of pharmacogenetic testing to be over 2,000 USD 49 . Thus, both genotyping and developing tools for translating pre-existing genome-wide genotype data into clinical recommendations can be considered very reasonable healthcare investments.…”
Section: Discussionmentioning
confidence: 99%
“…A medical intervention is defined as cost-effective when it costs more than standard care, but the extra-cost is considered acceptable based on the improvements in clinical outcomes, according to what is usually defined as willingness to pay threshold [25]. There are a few published studies looking at the cost-effectiveness of pharmacogenetic testing in guiding antidepressant prescription compared to standard care [26][27][28]. They reported evidence of cost-effectiveness compared to standard care, even though they were based on simulated clinical outcomes using input data from short-term clinical trials, while results coming from longer follow-up non-sponsored studies are lacking.…”
Section: Barriers To the Clinical Implementation Of Pharmacogeneticsmentioning
confidence: 99%
“…However, another study analyzing the cost-effectiveness of introducing a pharmacogenetic test (NeuroIDgenetix) in treatment plans for major depression provides a different perspective [3]. It mentions that, in 2016, the total per-patient economic burden of major depressive disorder was US $34,585.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…It mentions that, in 2016, the total per-patient economic burden of major depressive disorder was US $34,585. After integrating the pharmacogenetic test in treatment plans, the charge reduced to US $27,099, which saved the economy approximately US $7,486 [3].…”
Section: Cost-effectivenessmentioning
confidence: 99%